OPTIMALISASI POLA PEMANFAATAN PRODUK PERTANIAN LOKAL DALAM MEMENUHI KEBUTUHAN HOTEL BERBINTANG DI KOTA DENPASAR - Ratih Pertiwi, Putu; Widyatmaja, I GN.; Jamin Ariana, Nyoman (Jurnal Analisis Pariwisata; Vol 17 No 1 (2017): Jurnal Analisis Pariwisata (Oktober 2017), 2017)
The purpose of this research is to determine the problems faced related to utilization of local agricultural products to meet the needs of food and beverage at the star - grading hotel in Denpasar. Also to analyze strategies to overcome the problem of the utilization of local agricultural products to meet the needs of food and beverage at the star - grading hotel in Denpasar. Since the existence of the discours talked about the utilization of local agricultural products and it has become the warm issues lately among the public, this is caused by the restriction of products imported into Indonesia.We choosed several star - grading hotels in Denpasar as samples, analyzed by qualitative descriptive analysis method supported by IFAS and EFAS analyzis, as the result it is known that majorityof star - grading hotel in Denpasarhave been using local agricultural products for their food and beverage, they order those local products such as local rice, local fruits, local vegetables, local meats, local herbs, and local flowers from th elocal suppliers, consideringthat they offer authentic local menu for the guest and it required the authentic local flavors, also considering reasonable – tend to cheaper prices and faster delivery. However, they still have to face the problems: they are not able to avoid to order the imported product for ther food and beverage due to the some particular menus (foreign menus) that they offer to the guests which are the main ingredients of them are imported products and it has the same consideration is to create and maintain the authentic flavours of foreign menus.